Extensions to the HISA Standard – the SynEx Computing Environment - Grimson, W.; Jung, B.; van Mulligen, E. M.; van Ginneken, A.; Pardon, S.; Sottile, P. A. (Methods of Information in Medicine, 2002)
Objectives: This paper reports on the integration work required to support the delivery of healthcare. Specifically, four elements are included being: the DHE (a standards based distributed healthcare environment), Synapses which is a patient record server, XML as a technology to deliver records, and finally two client applications that facilitate structured data entry (SDE) and the remote booking of specialist services. Methods: A general motivation for the work is presented and augmented on hand of a clinical scenario. Additionally, the adoption of a middleware approach is reviewed. The role of computerised patient records is described followed by an account of a federated record server. The approach favoured by standards bodies in utilising XML is covered and the tailoring to suit the needs of the integration is explained. The main practical challenges in achieving integration are presented, one of these being the mapping between the DHE data model and the Synapses server record architecture.Results: The described environment has been demonstrated to provide the functionality that is required and in addition it has been shown that the engineering challenges can be met in a controlled and orderly manner.Conclusions: The role of the DHE middleware component acting as an ‘anchor’ has been shown to be a valid one onto which other specialised components can be added to provide a richer service environment. Additionally, it has been demonstrated that XML is a good candidate technology that facilitates connectivity to client applications over an extranet. The demands inherent in both the clinical scenario and the computerised patient record can be met by the computing environment described in the paper.
Keywords: Hospital information system; distributed healthcare environment; electronic patient record; record server; structured data; XML technology